Integrating English subject materials into Islamic boarding school curriculum context: Insights from Aceh, Indonesia - Habiburrahim Habiburrahim; Muhammad Muhammad; Luthfi Auni; Hafidhah Hafidhah; Ika Kana Trisnawati (Studies in English Language and Education, 2022)
Issues surrounding curriculum integration have been discussed worldwide. Some argue that curriculum integration contributes meaningfully to empowering students’ multi knowledge and skills, while others claim that curriculum integration has detrimental effects on teachers and students’ study load. This qualitative study investigates the English teachers’ and Islamic boarding school principals’ perceptions of integrating English subject materials of Curriculum 2013 into the Islamic boarding school curriculum context. Eleven participants (two Islamic boarding school principals and nine English teachers teaching at two Junior Islamic boarding schools in Banda Aceh) were selected purposively. The findings indicate that integrating English materials into the Islamic boarding school curriculum positively contributes to developing students’ general and Islamic-related knowledge. The results also suggest that the integration of English materials into the Islamic boarding school curriculum can be performed by switching the listed materials in the syllabus of Curriculum 2013 with the Islamic-related materials. The study unveils that among these curricula integration challenges are the inadequacy of Islamic-related knowledge that the teachers master and the subject overload. These two main issues are the main challenges to integrating the English materials into the Islamic boarding school curriculum.